2020
DOI: 10.1111/mec.15427
|View full text |Cite
|
Sign up to set email alerts
|

High genomic diversity in the bank vole at the northern apex of a range expansion: The role of multiple colonizations and end‐glacial refugia

Abstract: The history of repeated northern glacial cycling and southern climatic stability has long dominated explanations for how genetic diversity is distributed within temperate species in Eurasia and North America. However, growing evidence indicates the importance of cryptic refugia for northern colonization dynamics. An important geographic region to assess this is Fennoscandia, where recolonization at the end of the last glaciation was restricted to specific routes and temporal windows. We used genomic data to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(101 citation statements)
references
References 138 publications
(187 reference statements)
8
93
0
Order By: Relevance
“…Furthermore, when studying gene expression in wild populations there are additional sources of variation due to the natural heterogeneity of the sample (Kozera and Rapacz, 2013;Huang and Agrawal, 2016). In this study we have identified two strong pairs of RGs for the use in RT-qPCR studies of the bank vole, an emerging model species for evolutionary and epidemiological studies (Marková et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, when studying gene expression in wild populations there are additional sources of variation due to the natural heterogeneity of the sample (Kozera and Rapacz, 2013;Huang and Agrawal, 2016). In this study we have identified two strong pairs of RGs for the use in RT-qPCR studies of the bank vole, an emerging model species for evolutionary and epidemiological studies (Marková et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…studies and represented the three latitudinal zones identified based on the combined information from phylogenetic analyses of mitochondrial DNA sequences (Filipi et al, 2015) and clustering of genomic data (Marková et al, 2020): southern refugial (n = 6), which includes the areas of glacial refugia in the Mediterranean region, northern apex (n = 7), which includes Great Britain and Fennoscandia as the apex areas of the northward end-glacial colonization; and central (n = 8), including samples from the area between southern and northern regions, which has a mixed history of glacial survival and post-glacial colonization (Filipi et al, 2015;Marková et al, 2020).…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…MtDNA control region sequences of Myodes glareolus were used as a comparison to A. amphibius. All sequences were obtained from [26,27] and multiple alignments were computed based on location, before calculating population genetics statistics for each.…”
Section: Arvicola Amphibius: Population Genetics Statisticsmentioning
confidence: 99%